INFLUENCE OF PERFORMANCE MANAGEMENT ON THE PERFORMANCE OF TELECOMMUNICATION INDUSTRY IN KENYA - Rukumba, Steven; Iravo, Prof. Mike A.; Kagiri, Dr. Assumptah (Human Resource and Leadership Journal, 2019)
Purpose: The purpose of this study was to establish the influence of performance management on performance of telecommunication industry in Kenya Methodology: This study adopted both descriptive and correlational research designs. The study population was 300 senior management employees in all the four telecommunication firms in Kenya, which include, Safaricom, Airtel, Telkom and Equitel. The study used proportional sampling in selecting the managers from the four telecommunication firms. A sample size of 150 was arrived at using Fisher formula. Primary data was collected using structured questionnaires. Simple and multiple regression models were used to analyze the data using statistical package for the social sciences (SPSS version 20). Descriptive and inferential analysis was used to analyze the data. Results: Correlation analysis showed that performance management and the performance of telecommunication industry are positively and significantly associated. Further, regression analysis indicated that performance management has a positive and significant effect on performance of telecommunication industry in Kenya. The hypothesis results indicated that there is a significant relationship between performance management and the performance of telecommunication industry in Kenya. Recommendations: Based on the findings, the study recommended the need for telecommunication firms to strengthen their performance management aspects. These are: enhance employee rating, setting standards for employees, fostering teamwork among personnel, encouraging communication between employees and management and effective planning in the organization. The strengthening of these aspects will result to improved performance in the telecommunication industry.